Prognostic significance of the novel nutrition-inflammation marker of lymphocyte–C-reactive protein ratio in patients with nasopharyngeal carcinoma receiving concurrent chemoradiotherapy - Hua, Xin; Long, Zhi-Qing; Wang, Si-Fen; Xu, Fei; Wang, Meng-Di; Chen, Jia-Yi; Zhang, Yu-Ling; Ni, Wei-Qiong; Gao, Yun-Sheng (Frontiers in Nutrition, 2023)
Background: Recent studies indicate that the novel lymphocyte-C-reactive protein ratio (LCR) is strongly associated with the survival of various tumors, but its prognostic value in nasopharyngeal carcinoma (NPC) is understudied. This study aimed to explore the relationship between the LCR and overall survival (OS) in NPC and to develop a predictive model. Methods: A total of 841 NPC patients received concurrent chemoradiotherapy (CCRT) were retrospectively enrolled and randomly divided into training cohort (n=589) and validation cohort (n=252). Univariate and multivariate Cox analyses were performed to identify variables associated with OS and construct a predictive nomogram. The predictive accuracy of the nomogram was evaluated and independently validated. Results: The LCR score differentiated NPC patients into two groups with distinct prognoses (HR=0.53; 95% CI: 0.32-0.89, P=0.014). Multivariate analysis showed that age, T stage, N stage, EBV-DNA status, and LCR score were independently associated with OS and a predictive nomogram was developed. The nomogram had a good performance for the prediction of OS [C-index=0.770 (95% CI: 0.675-0.864)] and outperformed the traditional staging system [C-index=0.589 (95% CI: 0.385-0.792)]. The results were internally validated using an independent cohort. Conclusions: The novel nutrition-inflammation marker of LCR could serve as a simplified, affordable, easy-to-obtain, non-invasive, and readily promotive prognostic marker for NPC patients received CCRT, and the LCR-based prognostic nomogram outperformed the conventional staging system in terms of predictive power.